A Life Dedicated to Art - Ilyos Kuvatov (International Journal on Integrated Education, 2022)
In this article you can learn about the creative activity of the Chamber Orchestra of National Instruments "Sogdiana". You will get acquainted with the great achievements of the team over the years in the pursuit of meaningful and productive creativity